2020
DOI: 10.1111/1753-0407.13075
|View full text |Cite
|
Sign up to set email alerts
|

Associations between general and abdominal obesity and incident diabetic neuropathy in participants with type 2 diabetes mellitus

Abstract: Background: Previous epidemiological evidence on the sex-specific association of obesity, particularly abdominal obesity, as reflected by larger waist circumference (WC), with incident diabetic neuropathy (DN) remains limited. Methods: We used data from a patient cohort with a median 10-year history of type 2 diabetes mellitus at the time of recruitment. A composite outcome of four types of predefined DN (Neuro 1-4) was used as the outcome of interest. Because of sex differences in abdominal obesity, analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…Abdominal obesity is recognized as one of the important risk factors of cardiometabolic diseases [ 4 ], diabetes [ 5 ], and diabetic complications [ 6 ]. Interestingly, several studies reported that the distribution of adipose tissue rather than the total amount is more crucial in the development of vascular complications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal obesity is recognized as one of the important risk factors of cardiometabolic diseases [ 4 ], diabetes [ 5 ], and diabetic complications [ 6 ]. Interestingly, several studies reported that the distribution of adipose tissue rather than the total amount is more crucial in the development of vascular complications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies did not assess the association between obesity indexes and renal outcome stratified by sex. As an indicator of upper body adipose tissue distribution and abdominal obesity, waist circumference (WC) and waist-to-height ratio (WHtR) are considered a potential anthropometric measure of obesity ( 18 ). Thus, in the present study, we sought to assess the association between obesity (defined by WC, WHtR, and BMI) and diabetic nephropathy (DN) separately among men and women with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we sought to concurrently investigate the association of WC, WHtR, and BMI with incident DN using data from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study, which was a randomized, multicenter, double 2 × 2 factorial trial in 10,251 patients with T2DM ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prediction equations mentioned above permit studies of LBM or FM without dual-energy x-ray absorptiometry or imaging technologies. In this context, we conducted a post hoc analysis to investigate the association of predicted LBM and FM with incident DN using data from the ACCORD study, which was a randomized, multicenter, double 2 × 2 factorial trial in 10,251 patients with type 2 diabetes mellitus (T2DM) ( 22 ).…”
Section: Introductionmentioning
confidence: 99%